University Reform of 1918: Establishment of the Continental Network of Scientific, Educational and Student Community in Latin America - A. A. Schelchkov (Концепт: философия, религия, культура, 2021)
The transformation of the university system in Latin America, initiated by the reform in Argentina in 1918, marked the beginning of a period of democratization and modernization of society. The university reform was the result of a stubborn and dramatic struggle of students against the clerical-aristocratic order in the universities of Argentina. Ideologically, the movement was based on radical anti-clericalism, on the ideas of the conflict of generations, the special role of the young, on the Kulturtraegerism, on the concept of Arielism — a term coined by Enrique Rodo. The student movement, supported by progressive intellectuals and left-wing political parties, almost from the point of its inception, created a network of contacts and solidarity with other countries of the continent, which showed its high efficiency in disseminating ideas, political programs, and forms of struggle. This ability of the intellectual movements to create cross-border networks of influence and activism is relevant today and not only in Latin America. Thanks to this, the reform spread throughout the continent with various and sometimes contrary results, somewhere very successfully, and somewhere met with fierce resistance. The further ideological evolution of the movement and its leaders led to the emergence of new ideological and political currents, such as revolutionary nationalism, which became the dominant political trend in Latin America in the 20th century world. The spread of revolutionary nationalism, the main ideologist of which was the student leader in Peru, Victor Raul Haya de la Torre, relied on the same network of youth structures that led to the spread of the movement for university reform. The reform movement also resulted in the emergence of powerful left-wing movements of the intellectuals, such as the Latin American Union, closely associated not only with the student movement, but also with the labor movement. University reform was not only a political, but also a cultural phenomenon that marked a profound change in Latin American society, which chose the path of modernization of all spheres of life. This work is devoted to the study of this process.